Perbedaan Pengaruh Pemberian SWD Dan Mobilisasi Sendi Terhadap Peningkatan Kemampuan Fungsional Bahu - Retno Widaningrum; Fransisca Xaveria Hargiani; Wahyu Teja Kusuma; Nurul Halimah (Jurnal Keperawatan Muhammadiyah, 2021)
Objective: Frozen shoulder is a condition that often cause pain, joint stiffness, and limited of the shoulder joint, resulting in decreased functional ability for sufferers. Although the exact cause isn’t known, frozen shoulder arises due to an inflamatory reaction processes, and systemic disease disorders. The functional ability of the shoulder due to frozen shoulder using physiotherapy interventions. The pupose of this study was to determine the difference in the effect of giving Ultrasound and SWD compared to Ultrasound and mobilization of the shoulder joint in improving the functional ability of the shoulder. Methods: This research method is Quasi-experimental. The population sample involved 14 people who were determined using the Isaac and Michael table. There was divide into a control group and an experimental group, which consisted of 7 people. The control group was given Ultrasound and SWD, while the experimental group was given Ultrasound and mobilization of the shoulder joint. The data is collected using the SPADI questionnaire. The collected data were tested for normality using the Shapiro Wilk method and analyzed using the independent t-test.Results: There are differences in the effect of giving Ultrasound and SWD compared to Ultrasound and mobilization of the shoulder joint in improving the functional ability of the shoulder with a significant value of < 0.001Conclusion: The proves that the Ultrasound and mobilization of the shoulder joint are more influential in improving the functional ability of the frozen shoulder.